EFL Vietnamese Students towards Language Learning Autonomy - Thao, Phan Thi Kim (UICELL, 2018)
Language autonomy is one of aspects in second language acquisition.  It becomes vital theme  for many scholars and researchers to investigate how language learners take responsibility for  their study. The current paper attempts to examine language autonomy strategies were used  EFL Vietnamese students to  engage the language process as well as EFL teachers’ perceptions towards students’ language learning autonomy. The study used mixed research method. There were 246 participants consisting of 238 English major students and 8 EFL teachers were surveyed by questionnaire and semi-structured interview to indicate  their own perceptions on  language learning autonomy. The result showed high percentage of learners are independent in  learning and EFL teachers’ perceptions on  students’ language learning. Keywords: Learning strategy, language autonomy, EFL students.